Factibilidad de una empresa productora de vino artesanal de maracuyá en la ciudad de Loja y comercialización en la provincia de Loja - Medina Maldonado, Daniela Alejandra (2025)
This project aims to develop a natural product as an option in the province of Loja, so that it can be consumed at gatherings with friends or family to make the moment meaningful and unforgettable with the people they esteem most, we chose to use natural raw material of the locality, as is the fruit of passion fruit, and through a process of elaboration we can obtain as it is the artisanal passion fruit wine with a unique and natural flavor. To start with the present project, a general objective has been designed: to elaborate a company that produces handmade passion fruit wine in the city of Loja and commercialize it in the province of Loja. Through this, specific objectives were proposed that served as a guide for this study. In order to execute this main objective, methods, techniques and procedures were proposed to scrutinize, develop and verify the clarity of the project. The methods implemented were the following: Deductive, which allowed based on the theoretical concepts related to the realization of an investment project to apply them in the development of market, technical, organizational, economic and financial studies; Inductive, as also used techniques for data collection used to have specific data from the surveys raised. The following techniques were adapted: Observation: This allowed us to know how the process of production and commercialization of passion fruit wine is currently carried out. Survey: Applied to a representative sample of the population of families in the province of Loja to determine the needs and preferences of the target market in relation to the consumption of passion fruit wine, very important information for the establishment of demand, supply and unsatisfied demand for the product to be produced. Total, number of surveys 397, total study population 448,966 families. The market study of this project shows that for the base year there is an unsatisfied demand of 719874 liters of passion fruit wine, deducing that in Loja there is a good market for the sale of this product. In addition, the project engineering establishes that for the first year the product to be offered will be 54750 liters of passion fruit wine, taking into account that 75% of the installed capacity in liters will be used. The economic and financial study establishes that the investment for the project is $256,965.10; 50% of this amount will be financed by the company's partners and the remaining 50% will be granted by a bank with an annual interest rate of 16% for a term of 10 years. It is worth mentioning that the company's Internal Rate of Return (48.79%) is higher than the established interest rate, so it is efficient to carry out the project and that the Net Present Value is $ 389,529.36. The entire investment will be recovered in a period of 2 years, 0 months and 22 days. Based on the results obtained, it is recommended to implement the project since it will provide significant profitability and sustainability for its investors and will generate productive development in the city of Loja and contribute to the generation of jobs for the citizens, contributing to the socioeconomic development of the province of Loja